Advances in Digital Forensics III IFIP International Conference on Digital Forensics , National Center for Forensic Science, Orlando Florida, January 28-January 31, 2007 - Craiger, Philip; Shenoi, Sujeet (IFIP Advances in Information and Communication Technology, 2007)
ADVANCES IN DIGITAL FORENSICS III Edited by: Philip Craiger and Sujeet Shenoi Digital forensics deals with the acquisition, preservation, examination, analysis and presentation of electronic evidence. Networked computing, wireless communications and portable electronic devices have expanded the role of digital forensics beyond traditional computer crime investigations. Practically every crime now involves some aspect of digital evidence; digital forensics provides the techniques and tools to articulate this evidence. Digital forensics also has myriad intelligence applications. Furthermore, it has a vital role in information assurance -- investigations of security breaches yield valuable information that can be used to design more secure systems. Advances in Digital Forensics III describes original research results and innovative applications in the emerging discipline of digital forensics. In addition, it highlights some of the major technical and legal issues related to digital evidence and electronic crime investigations. The areas of coverage include: - Legal Issues - Insider Threat Detection - Rootkit Detection - Authorship Attribution - Forensic Techniques - File System Forensics - Network Forensics - Portable Electronic Device Forensics - Evidence Analysis and Management - Formal Methods This book is the third volume in the annual series produced by the International Federation for Information Processing (IFIP) Working Group 11.9 on Digital Forensics, an international community of scientists, engineers and practitioners dedicated to advancing the state of the art of research and practice in digital forensics. The book contains a selection of twenty-four edited papers from the Third Annual IFIP WG 11.9 Conference on Digital Forensics, held at the National Center for Forensic Science, Orlando, Florida, USA in the spring of 2007. Advances in Digital Forensics III is an important resource for researchers, faculty members and graduate students, as well as for practitioners and individuals engaged in research and development efforts for the law enforcement and intelligence communities. Philip Craiger is an Assistant Professor of Engineering Technology and Assistant Director for Digital Evidence at the National Center for Forensic Science, University of Central Florida, Orlando, Florida, USA. Sujeet Shenoi is the F.P. Walter Professor of Computer Science and a principal with the Center for Information Security at the University of Tulsa, Tulsa, Oklahoma, USA.